Emotional Intelligence and Competency Factors in Explaining Teacher Performance - Putra, Okta Eka; Vany, Prisi Aulia Eris; Purwadisastra, Dikdik (Indonesian Scientific Publication, 2025)
This scholarly inquiry seeks to elucidate the characterisation and impact of emotional intelligence, professional competence, and pedagogical performance within the KH. Zainal Mustafa Cluster is located in Cikalong Wetan. The methodological framework adopted for this study encompasses both descriptive and verification methodologies, employing quantitative research techniques. The demographic scope of this investigation encompasses all elementary school educators affiliated with the KH. Zainal Mustafa Cluster in Cikalong Wetan comprises a total of nine educational institutions and includes 91 teaching professionals. The sampling methodology in this research utilises a non-probability sampling technique, precisely a saturated sampling approach, thereby ensuring that every individual within the population is included in the sample. The outcomes derived from the descriptive analysis reveal that the variable of emotional intelligence is categorised as high, the variable of competence is classified as good, and the variable of teacher performance is also designated as exemplary. The findings derived from the partial determination assessment indicated that the emotional intelligence variable exerted an influence of 22.4% on the performance of educators, whereas competence demonstrated a 24.7% effect on educator performance; when considered concurrently, the combined impact of emotional intelligence and competence on teacher performance was observed to be 40%. The outcomes of the hypothesis testing revealed that, in isolation, both the emotional intelligence and competency variables exhibited a statistically significant effect on teacher performance, characterised by a positive direction of influence; furthermore, it was determined that collectively, the emotional intelligence and competency variables significantly impacted the teacher performance within the KH. Zainal Mustafa Cluster is located in Cikalong Wetan.